Development Of An Islamic Group Guidance Model Based On KBS (Knowledge Based Society) - Ari Setyawan, David (IAIN Kudus, 2026)
Development Of An Islamic Group Guidance Model Based On KBS (Knowledge Based Society). This research aimed to develop a model for Islamic group guidance based on the KBS (Knowledge Based Society) program. This model has significant potential for effectiveness and maximum results. The subjects were fifth-year Islamic Guidance and Counseling students. The research method used was quantitative research, with data collection aided by questionnaires, interviews, and observations.The pre-test results showed that there were 6 students with an average score of 76.16. After being given group guidance, the 6 students were asked to complete the post-test and the average result was 108.83. Based on the results of the paired sample t-test analysis, it can be obtained that the calculated t is greater than the t table, namely 37.041> 2.571 and Sig. (2 tailed) = 0.000 < 0.05, then Ho is rejected and Ha is accepted. So it can be concluded that the Islamic group guidance model based on KBS (Knowledge Based Society) is proven to be effective. The characteristics of the KBS (Knowledge Based Society) approach in Islamic group guidance lie in the activity stage which presents the concept of a social order which places the mastery, creation, processing and utilization of knowledge and information technology (ICT) as the main drivers of economic, social and cultural growth.Keywords: Group Guidance, Islamic Group Guidance, Knowledge-Based Society